2001
DOI: 10.1002/1521-4141(200104)31:4<1122::aid-immu1122>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Human anergic/suppressive CD4+CD25+ T cells: a highly differentiated and apoptosis-prone population

Abstract: Anergic/suppressive CD4+CD25+ T cells exist in animal models but their presence has not yet been demonstrated in humans. We have identified and characterized a human CD4+CD25+ T cell subset, which constitutes 7–10 % of CD4+ T cells in peripheral blood and tonsil. These cells are a CD45RO+CD45RBlow highly differentiated primedT cell population that is anergic to stimulation. Depletion of this small subset from CD4+ T cells significantly enhances proliferation by threefold in the remaining CD4+CD25– T cells, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
316
4
5

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 398 publications
(368 citation statements)
references
References 34 publications
43
316
4
5
Order By: Relevance
“…5). As previously reported, T reg died more quickly than T eff [12]. Furthermore, IL-2 rescued significantly more T reg than T eff from cell death, which reflects the well known dependency of highly purified CD4 + CD25 high cells on exogenous IL-2 in vitro [35,36].…”
Section: T Reg From Ms Patients Do Not Display Enhanced Sensitivity Tsupporting
confidence: 82%
See 1 more Smart Citation
“…5). As previously reported, T reg died more quickly than T eff [12]. Furthermore, IL-2 rescued significantly more T reg than T eff from cell death, which reflects the well known dependency of highly purified CD4 + CD25 high cells on exogenous IL-2 in vitro [35,36].…”
Section: T Reg From Ms Patients Do Not Display Enhanced Sensitivity Tsupporting
confidence: 82%
“…Within the human CD4 + subset only cells coexpressing high levels of CD25 appear to have potent regulatory function [6,7]. CD4 + CD25 high regulatory T cells (T reg ) are anergic to antigenic stimulation and actively downregulate activation and expansion of conventional T lymphocytes in a cell-contact-dependent and cytokine-independent manner [5, [8][9][10][11][12][13]. Although the molecular interactions and signaling pathways that are critical for their generation and function are nut fully elucidated, T reg require forkhead transcription factor scurfin encoded by the Foxp3 gene, which appears to control their development and regulatory properties [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Human CD25 + T cells also have the phenotype of activated/memory T cells in that they are predominantly CD45RO + and a variable number also express MHC class II antigens. In one study 18, they were also shown to be CD45RO + and CD45RB low which is consistent with T cells which have been restimulated by antigen multiple times. The expression of CD122 (IL-2R β-chain) was easily detectable on human CD25 + T cells, while its expression on murine CD25 + cells is controversial.…”
Section: Identification Of Cd4+cd25+ T Cells In Manmentioning
confidence: 63%
“…Three papers in this issue 14 15 16 and three papers 17 18 19 appearing elsewhere now describe the properties of human CD4 + CD25 + T cells. Given the obsession of most cellular immunologists with the concept of separating functionally distinct populations of cells based on their differential expression of membrane antigens, it is surprising that 6 yr elapsed between the identification of these cells in the mouse and the confirmation of their existence in man.…”
Section: Identification Of Cd4+cd25+ T Cells In Manmentioning
confidence: 99%
See 1 more Smart Citation